2012
DOI: 10.4236/ojpchem.2012.21004
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid-loaded Cellulose Acetate Electrospun Nanofibers: Thermal Properties, Mechanical Properties, and Drug Release Behavior

Abstract: The gallic acid-loaded electrospun cellulose acetate fibers were successfully prepared. The fiber containing 2.5% gallic acid was smooth surface but observed drug flake on the surface of the fiber when increasing drug content. The thermal properties, mechanical properties and drug release behavior of the fibers were investigated comparing to the corresponding films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Some sustained-release formulations of gallic acid like gallic acid-loaded cellulose acetate electrospun nanofibers (44) and gallic acid-loaded electrospun poly(L-lactic acid) fiber (45) were developed and investigated for their in vitro release properties, but sufficient data on the effect of pharmacokinetic parameters are not available. Due to the nontoxic nature of phospholipids, the phospholipid delivery systems are favored than other delivery systems which utilize polymer.…”
Section: Pharmacokinetic Parametersmentioning
confidence: 99%
“…Some sustained-release formulations of gallic acid like gallic acid-loaded cellulose acetate electrospun nanofibers (44) and gallic acid-loaded electrospun poly(L-lactic acid) fiber (45) were developed and investigated for their in vitro release properties, but sufficient data on the effect of pharmacokinetic parameters are not available. Due to the nontoxic nature of phospholipids, the phospholipid delivery systems are favored than other delivery systems which utilize polymer.…”
Section: Pharmacokinetic Parametersmentioning
confidence: 99%
“…Still, the capacity to design and engineer systems that allow a gradual and continuous release of EOs at concentrations below the cytotoxic, while using the electrospinning technique, has been improving and has already revealed very promising results. In fact, studies have shown that CA-based electrospun nanostructures loaded with EOs to display a higher capacity to retain water and aromatic compounds, thus reducing the initial drug burst and extending release over time, this way increasing the effectiveness of the therapy above other non-reticulated systems [179,180]. Table 7 presents some of the most recent EOs loaded electrospun systems containing cellulose, CA or nanocellulose formulations, in which the above-mentioned properties and outcomes are the most noticeable.…”
Section: Natural Extractsmentioning
confidence: 99%
“…Cellulose acetate (CA) fibres and membranes have important biomedical applications in affinity membranes and drug delivery [1]. The development of experimental biomedical products continues to involve solution blending of the polymer with other therapeutic molecules and compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Research has led to the fabrication of various functional materials including antibacterial CA nanofibres containing AgNO3 [2], nanofibres for therapeutic delivery of active compounds, such as vitamins A and E [3], curcumin [4], nicotine [5], naproxen [6], gallic acid [1], gingerol [7], tetracycline hydrochloride [8], ketoprofen [9], the assembly of topical drug delivery carriers containing non-steroidal anti-inflammatory drugs (NSAIDs) [10], and edible nanofibrous films containing egg albumen [11].…”
Section: Introductionmentioning
confidence: 99%